17β-Estradiol induces cyto-genotoxicity on blood cells of common carp (Cyprinus carpio). (January 2018) - Orozco-Hernández, Luis; Gutiérrez-Gómez, Adriana Andrea; SanJuan-Reyes, Nely; Islas-Flores, Hariz; García-Medina, Sandra; Galar-Martínez, Marcela; Dublán-García, Octavio; Natividad, Reyna; Gómez-Oliván, Leobardo Manuel
Abstract: 17β-Estradiol, a natural hormone present at high concentrations in aquatic ecosystems, affects and modifies endocrine function in animals. In recent years research workers have expressed concern over its potential effects on aquatic organisms; however, little is known about its capacity to induce genetic damage or the pro-apoptotic effects of such damage on fish. Therefore, this study aimed to evaluate 17β-estradiol-induced cyto-genotoxicity in blood cells of the common carp Cyprinus carpio exposed to different concentrations (1 ng, 1 μg and 1 mg L −1 ). Peripheral blood samples were collected and evaluated by comet assay, micronucleus test, determination of caspase-3 activity and TUNEL assay at 12, 24, 48, 72 and 96 h of exposure. Increases in frequency of micronuclei, TUNEL-positive cells and caspase-3 activity were observed, particularly at the highest concentration. In contrast, the comet assay detected significant increases at 24 and 96 h with the 1 μg and 1 ng L −1 concentrations respectively. The set of assays used in the present study constitutes a reliable early warning biomarker for evaluating the toxicity induced by this type of emerging contaminants on aquatic species. Graphical abstract: Image 1 Highlights: This study aimed to evaluate 17β-estradiol-induced cyto-genotoxicity in Cyprinus carpio . Increases in frequency of micronuclei, caspase-3 activity and TUNEL-positive cells were observed. The comet assay detected significant increases at 24 and 96 h with the 1 μg and 1 ng L −1 of E2. 17β-Estradiol induces cyto-genotoxicity on C. carpio .